2021
DOI: 10.3389/fonc.2021.768493
|View full text |Cite
|
Sign up to set email alerts
|

High-LET Carbon and Iron Ions Elicit a Prolonged and Amplified p53 Signaling and Inflammatory Response Compared to low-LET X-Rays in Human Peripheral Blood Mononuclear Cells

Abstract: Understanding the differences in biological response to photon and particle radiation is important for optimal exploitation of particle therapy for cancer patients, as well as for the adequate application of radiation protection measures for astronauts. To address this need, we compared the transcriptional profiles of isolated peripheral blood mononuclear cells 8 h after exposure to 1 Gy of X-rays, carbon ions or iron ions with those of non-irradiated cells using microarray technology. All genes that were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 102 publications
(116 reference statements)
0
10
0
Order By: Relevance
“…Following exposure to 0.5 Gy of either gamma rays, protons, carbon ions or alpha particles, it was observed that DSB-protein complexes persisted longer in the cell nucleus following higher LET irradiation [ 153 ]. In a similar study of 1 Gy X-ray, or carbon or iron ions, DSB foci in peripheral blood mononuclear cells were slower to resolve from high- LET radiations [ 154 ]. The dependence of high LET on HRR for DNA repair and the reduced rate of DNA repair in general suggested that high-LET radiation may reduce the efficiency of NHEJ [ 153 , 155 ].…”
Section: Signal Transduction By High and Low Letmentioning
confidence: 99%
See 4 more Smart Citations
“…Following exposure to 0.5 Gy of either gamma rays, protons, carbon ions or alpha particles, it was observed that DSB-protein complexes persisted longer in the cell nucleus following higher LET irradiation [ 153 ]. In a similar study of 1 Gy X-ray, or carbon or iron ions, DSB foci in peripheral blood mononuclear cells were slower to resolve from high- LET radiations [ 154 ]. The dependence of high LET on HRR for DNA repair and the reduced rate of DNA repair in general suggested that high-LET radiation may reduce the efficiency of NHEJ [ 153 , 155 ].…”
Section: Signal Transduction By High and Low Letmentioning
confidence: 99%
“…p53 protein is recruited to DSB lesions containing ATM, ATR, and phosphorylated histone H2AX (γH2AX) [ 131 ]. The specific rearrangements of phosphorylation on p53 at 18 amino acids are critical for the modulation of its downstream activity [ 148 , 154 , 161 ]. Following DDR activation by radiation, p53 is rapidly dephosphorylated (dephosphosphorylated-S37, -S46, and -T55—apoptosis), while other sites are phosphorylated (phospho-S15—cell cycle arrest) [ 148 , 161 , 162 ].…”
Section: Signal Transduction By High and Low Letmentioning
confidence: 99%
See 3 more Smart Citations